EVALUATION OF A PEDIATRIC LIQUID FORMULATION TO IMPROVE 6-MERCAPTOPURINE THERAPY IN CHILDREN. Issue 1 (14th December 2015) - de Beaumanis, Tiphanie Adam; Hjalgrim, Lisa Lynqsie; Nersting, Jacob; Breitkreutz, Jörg; Bertrand, Yves; Stanulla, Martin; Leverger, Guy; Baruchel, André; Schmiegelow, Kjeld; Jacqz-Aigrain, Evelyne
Abstract : Background: 6-mercaptopurine (6-MP), a key drug for treatment of acute lymphoblastic leukemia (ALL), has until recently had no adequate formulation for pediatric patients. Several approaches have been taken but the only oral paraben-free 6-MP liquid formulation named Loulla was developed and evaluated in the target population. Preclinical and clinical evaluation was performed according to a Pediatric Investigation Plan, in order to apply for a Pediatric Use Marketing Authorization. Methods: The pre-clinical study assessed the maximum tolerated dosage-volume and evaluated local mucosal toxicity of 28 daily administrations in treated compared to controls gold hamsters. The multi-centre clinical study was single-dose, open-label, crossover trial, conducted in 15 ALL children during maintenance therapy. The bioavailability and palatability of a single 50 mg fixed dose of Loulla compared to 50 mg registered tablets were evaluated in a random order on two consecutive days. Seven blood samples over 9 hours were obtained each day at to determine 6-MP pharmacokinetic parameters, including Tmax, Cmax, AUC0–9 and AUC0–∞. A questionnaire adapted to children testing Loulla palatability and preference for either Loulla or the usual 6-MP tablet was completed. Occurrence of adverse events was determined at study visits by vital sign measurements, patient's spontaneous reporting, investigator's questioning and clinical examination. Results: The preclinical study in gold hamsters showed that dosage-volume of 75 mg/kg/day was well tolerated. The relative bioavailability of liquid Loulla formulation compared to the reference presentation is 76% for AUC0-9 and AUC0-∞ and 80% for Cmax. The taste of Loulla and the mouth feeling after ingestion compare favorably to the tablet. No adverse event occurred. Conclusion: Pharmacokinetic, palatability and safety data support the use of Loulla in children.